2010
DOI: 10.1148/radiol.10100626
|View full text |Cite
|
Sign up to set email alerts
|

Gray- and White-Matter Changes 1 Year after First Clinical Episode of Multiple Sclerosis: MR Imaging

Abstract: WM damage was detectable early and involved most fiber tracts in patients with MS, but it did not worsen significantly during the 1st year after clinical onset. In contrast, GM damage was not detectable at the time of clinical onset, but a significant decrease in cortical and deep GM volume was observed at 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
71
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 45 publications
7
71
1
2
Order By: Relevance
“…22 No significant differences were found in whole-brain, global GM, WM, and/or cortical volumes between the 2 groups. This confirms the results of some recent studies that showed that selective regional, but not global, atrophy occurs from clinical onset to conversion to clinically definite MS. [17][18][19][20] This study provides strong evidence that regional GM atrophy is exclusively confined to the SDGM and not to cortical regions in the first 4 years of disease duration. Our findings suggest, therefore, that future studies should concentrate more on understanding the pathogenetic mechanisms leading to selective SDGM rather than to cortical GM damage in patients with early RRMS.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…22 No significant differences were found in whole-brain, global GM, WM, and/or cortical volumes between the 2 groups. This confirms the results of some recent studies that showed that selective regional, but not global, atrophy occurs from clinical onset to conversion to clinically definite MS. [17][18][19][20] This study provides strong evidence that regional GM atrophy is exclusively confined to the SDGM and not to cortical regions in the first 4 years of disease duration. Our findings suggest, therefore, that future studies should concentrate more on understanding the pathogenetic mechanisms leading to selective SDGM rather than to cortical GM damage in patients with early RRMS.…”
Section: Discussionmentioning
confidence: 59%
“…[5][6][7] More recently, research has focused on determining the extent of GM pathology at the first clinical event in patients presenting with CIS [8][9][10][11][12][13][14][15][16] or on its evolution with conversion to clinically definite MS. [17][18][19][20] It has been reported that global GM volume measures are not sensitive enough to detect GM atrophy at the time of the initial attack.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, VBM has been used extensively in the analysis of brain atrophy in MS (Battaglini et al., 2009; Bendfeldt et al., 2009, 2010; Ceccarelli et al., 2008; Raz et al., 2010). We have used VBM to demonstrate that there were distinct associations between voxelwise GM loss and specific clinical disabilities (MacKenzie‐Graham et al., 2016).…”
Section: Introductionmentioning
confidence: 99%